If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + (X + 55) + (X + 38) = 180 Reorder the terms: X + (55 + X) + (X + 38) = 180 Remove parenthesis around (55 + X) X + 55 + X + (X + 38) = 180 Reorder the terms: X + 55 + X + (38 + X) = 180 Remove parenthesis around (38 + X) X + 55 + X + 38 + X = 180 Reorder the terms: 55 + 38 + X + X + X = 180 Combine like terms: 55 + 38 = 93 93 + X + X + X = 180 Combine like terms: X + X = 2X 93 + 2X + X = 180 Combine like terms: 2X + X = 3X 93 + 3X = 180 Solving 93 + 3X = 180 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-93' to each side of the equation. 93 + -93 + 3X = 180 + -93 Combine like terms: 93 + -93 = 0 0 + 3X = 180 + -93 3X = 180 + -93 Combine like terms: 180 + -93 = 87 3X = 87 Divide each side by '3'. X = 29 Simplifying X = 29
| 14/5x−14=4/5x−7/4 | | 12=7m-1+6m | | U=2a+2b | | X+3x-4=5(x+2) | | 6y-2=20 | | 18(2x+6)=6(3x+30) | | 40p-5=-5p-5 | | lne^4/5 | | 3x+7+5x=11+4x+8 | | 2x-6x=-2x | | 26+X^2=90 | | 6x^3+2x^2=10x-8 | | 5.8(x-4)=0.2x+24.8 | | -d+5=20 | | -6=1/3x-4 | | -350.55555556/1.8 | | 0.02x=x-12.25 | | 13x+32-9x=-24-4x | | 2(t-4)+9=-7 | | -631/1.8 | | -10+a=10 | | 6(4x-3)-(2+x)=55-2x | | -y+8=38 | | 8(8-4x)=-192 | | 2(2x+3)=21 | | H(x)=xsquared-8x+3 | | 2x+3-9x=25-7x | | 3(x-5)+8x=62+4x | | -3=m/9 | | -c+7=52 | | X+3x-3=-2x+5 | | 3.8x-5.9+7x=7.8x-20.3 |